Hall current and joule heating effects on peristaltic flow of a sisko fluid with mild stenosis through a porous medium in a tapered artery with slip and convective boundary conditions - El-dabe, Nabil T.M.; Mostapha, Doaa R. (Penerbit Universiti Kebangsaan Malaysia, 2020)
This work is arranged to investigate the Hall current and Joule heating effects on peristaltic flow of a Sisko fluid through a porous medium. The streaming is through tapered artery with mild stenosis. The influences of radiative heat transfer and chemical reactions are taken in consideration. Convective conditions are considered for heat and mass transfer. However, the slip conditions are adopted for the velocity distribution. The combined effects of viscous dissipation and radiation in energy expression are presented. Soret and Dufour features produce the coupled differential systems. The presumptions of the long wavelength and low Reynolds number are adopted to examine the governing equations of motion. The analytical solutions of these equations are given by two methods. The first one uses regular perturbation technique, which based on small wave number for small artery. The second one is based on utilizing the Homotopy perturbation technique. The approximate analytical solutions of the pressure rise and friction force are predestined along a numerical integration. The influences of various physical parameters of the problem are debated and depicted graphically through a set of figures. It is found that the axial velocity increases with the increase of Hall current parameter and with the decrease of Hartmann number. Also, it can be observed that the Brickmann number and Dufour number give rise to the fluid temperature. Meanwhile, reverse effect is observed towards concentration for both Schmidt number and chemical reaction number. Furthermore, the stream lines are graphically shown.